The Relationship Between Toxoplasmosis and Prostate Cancer Patients: Hubungan Antara Toksoplasmosis dan Pasien Kanker Prostat - Shihab, Raghad N.; Sulaiman , Evan H.; El Abdeen, Atheer Abd elqader Zain (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Toxoplasmosis is one of the most common global life-threatening diseases among immunocompromised persons. It is not only a disease, but also a contributing factor to several pathological disorders, such as prostate cancer. Objectives. The purpose of the presented work is determining the prevalence regarding toxoplasmosis in Iraqi cancer patients and to connect that prevalence with the type of malignancy. Patients and Methods: This study included 115 male patients (75 with prostatic tumors and 40 with normal prostate glands) from Al-Amal National Hospital for Cancer Management was enrolled between December 15, 2023and July 1, 2024. Results: The study's results showed that prostate cancer patient group with the toxoplasmosis had the greatest IgG antibody level, measuring 52.64±1.16 UI/ml. The control group had 0.306±0.05 UI/ml. According to CMIA, all groups had seronegative IgM antibody levels. However, the mean PSA of the patients in this study was 66.72±0.51 ng/ml, compared to 2.48 ±0.04 ng/ml for the healthy control groups. Measuring IL-10 levels in samples were done by ELISA method showed a group of prostate cancer patients with toxoplasmosis has highest level 19.36 ±0.15 pg/ml, while the healthy control group has the lowest level of the same assay 12.78 ±0.13 pg/ml. However, illustrated that prostate cancer patient group with toxoplasmosis higher level significantly (P≤0.01) of IFNγ in comparation of the group of healthy control. Conclusion: Prostate inflammation is caused by the common parasite T. gondii, which encysts and causes chronic inflammation in prostate of any species, according to this work. The anti-inflammatory cytokines IL-10 and IFNγ were linked to an increased risk of prostate cancer infected with toxoplasmosis. Highlights: Toxoplasmosis contributes to prostate cancer risk via chronic inflammation. Analyzed IgG, PSA, IL-10, and IFNγ in prostate cancer patients. Elevated IL-10, IFNγ indicate toxoplasmosis increases prostate cancer susceptibility. Keywords: Toxoplasma gondii; IgM, IgG, Prostate cancer